Influencia de la madurez en el rendimiento y las propiedades fisicoquímicas del aceite esencial del fruto de naranjo tipo valencia - Zambrano Velásquez, Raúl Bienvenido (2019)
The aim of this research was to evaluate the effect of the state of maturity of the orange on the yield and the physical-chemical characteristics of the essential oil (AE) extracted from the peel. As a variant, three maturity stages were used (green, pintona, mature), defined by colorimetric analysis. The test was conducted with one DCA and three replications, while the experimental unit consisted of 30 oranges weighing approximately 5 kg, according to the evaporator requirement, which was used for the extraction of the EA, by means of the entrainment method. The extracted PE was evaluated for performance and physical properties: density, optical activity and refractive index. The chemical composition of the EA was determined by a gas chromatograph coupled to CG/MS mass spectrometry. The performance of AE was not significant, the values oscillated between 0.34-0.57%, as well as density 0.84 mL/ g refractive index 1.47, in the optical activity they shared statistical category the states of green maturity and matures with averages of 113.59º, respectively. In chemical composition, the majority component was limonene with 96%, regardless of the state of maturity. The remaining proportion corresponded, in minimum quantities, to the following components; the linalool that turned out better in green oranges; the pinene and myrcene where the state of maturity did not affect; for sabinene, octanal, ocinene, decanal and carane the treatments do not explain the presence of these compounds, according to the dichotomy analysis. It is concluded that it is possible to extract the AE indifentemente to the state of maturity.